Factors predisposing to worsening of sleep apnea in response to fluid overload in men - Gavrilovic, Bojan; Bradley, T. Douglas; Vena, Daniel; Lyons, Owen D.; Gabriel, Joseph M.; Popovic, Milos R.; Yadollahi, Azadeh (Sleep medicine, 2016)
•Presleep bioimpedance measures and neck circumference can predict susceptibility to fluid overload.•Men with larger pharyngeal tissue may be more susceptible to obstructive sleep apnea with fluid overload.•Fluid overloading results in more fluid accumulation in the neck. [Display omitted] Obstructive sleep apnea (OSA) is highly prevalent in patients with fluid-retaining conditions. Using bioimpedance measurements, previous studies have shown that the greater the amount of fluid redistributed from the legs to the neck overnight, the greater the severity of OSA. Our objective was to investigate factors that predispose the development or worsening of OSA in response to experimental fluid overload. Fifteen normotensive and non-obese adult men with and without OSA underwent polysomnography (PSG) during which normal saline was infused intravenously at a minimal rate to keep the vein open (control) or as a bolus of 22 ml/kg body weight (approximately 2 L) in a random order and crossed over after a week. Before and after sleep, neck circumference and bioimpedance were measured to calculate neck resistance, reactance, phase angle, and fluid volume. Subjects who experienced more than a twofold increase in apnea–hypopnea index (AHI) or obstructive AHI from control to intervention and had an AHI>10 during intervention were considered susceptible to the development or worsening of OSA. Baseline neck circumference and phase angle before saline infusion were independently associated with increased susceptibility to developing or worsening OSA in response to saline infusion. In non-obese men, a larger neck circumference and bioimpedance phase angle of the neck, which may be associated with larger pharyngeal tissue content, is associated with increased susceptibility for worsening of OSA in response to fluid overloading.